Uncovering the Perception of Digital Gold as Islamic Investment - Wicaksono, Ahmad Tibrizi Soni; Soetjipto, Budi Eko (Maliki Islamic Economics Journal, 2025)
This study aims to identify sentiments related to digital gold as Islamic investment in social media users. The study used Word cloud analysis, Sankey diagrams and sentiment dominance portion assessment through a natural language processing (NLP) approach. The study processed 1433 user responses from Facebook, Instagram, TikTok, X, and YouTube over the past year. The results show that there is scepticism in understanding Islamic investment through digital gold. Instagram, YouTube, and Tiktok are social media that dominate negative sentiment. Sentiment analysis shows that negative sentiment dominates the perception of social media users with a portion of 64.69%. The implications of the study direct the importance of public education to avoid a decline in investment interest. The limitations of the study include the range of opinions in one country using only five social media.